Answer:
![\displaystyle [6, -3]](https://img.qammunity.org/2023/formulas/mathematics/high-school/kdfaof241fj43m1m3jmnqhb8yi5axrjzqv.png)
Step-by-step Step-by-step explanation:
To begin this process, we will first select the second equation. Here is how the Substitution method wourks:
![\displaystyle \left \{ {{3x + 5y = 3} \atop {x + 2y = 0}} \right. \\ \\ \\ \left \{ {{y = 2x + 3} \atop {x = -2y}} \right. \\ \\ 3[-2y] + 5y = 3 \hookrightarrow -6y + 5y = 3 \hookrightarrow -y = 3; -3 = y, 6 = x \\ \\ \\ \boxed{[6, -3]}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ib5cgxqmvipirr20zxk83qs231tvq2wrww.png)
So, you substitute
for
and continue combining like-terms until you receive the y-value. You then plug this back into the system to get the x-value, which was what you saw.
I am joyous to assist you at any time.